Constitutional Legitimacy, Limitations, and Strengthening of State-Owned Enterprise Monopoly Supervision in Economic Development and Protection of Healthy Business Competition in Indonesia - Budi Joyo Santoso; Hamid, Adnan (Journal of Law, Politic and Humanities, 2025)
This study highlights the central role of State-Owned Enterprises (SOEs) in managing strategic sectors as a realization of the mandate of Article 33 of the 1945 Constitution of the Republic of Indonesia. This paper questions the legitimacy, constitutional limitations, and oversight mechanisms for monopoly rights granted by the President to SOEs, as well as the challenges of policy implementation in the context of national economic governance reform. The methodology used is a normative legal approach with conceptual analysis, legislation, and comparative studies with other countries. The study was conducted on key regulations such as Law No. 5 of 1999, Law No. 1 of 2025, and KPPU documents, supported by a review of Constitutional Court decisions. The analysis was conducted using legal hermeneutics and qualitative methods to interpret the constitutional limits and effectiveness of SOE monopoly supervision. The results of the discussion found that the constitutional legitimacy of SOE monopolies is indeed sourced from Article 33 of the 1945 Constitution, but their implementation must meet the requirements of efficiency, justice, and legal certainty. It was found that granting monopolies without periodic supervision and evaluation risks causing abuse of authority, market distortion, and discriminatory practices against other business actors. The KPPU's role as an independent supervisory body has proven strategic in preventing violations and correcting monopolistic policies inconsistent with the principles of fair competition. Strengthening oversight mechanisms, transparency of audit results, public involvement, and regular independent audits are needed as a foundation for adaptive and accountable governance. Recommendations for regulatory reform, effective KPPU involvement, and public participation are proposed to balance state interests and protection of business competition. The conclusion emphasizes that monopoly by state-owned enterprises is not an end in itself, but rather an instrument for realizing public welfare if implemented with transparency, strict oversight, and high accountability in accordance with the principles of constitutional economic democracy.